GENERATION Z FINANCIAL MANAGEMENT FROM A BEHAVIORAL FINANCE PERSPECTIVE: THE ROLE OF FINTECH, CONSUMPTIVE BEHAVIOR, FINANCIAL ATTITUDE, AND FINANCIAL PLANNING - Suhandi; Sri Mulyati; Hanafi Siregar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of financial technology (fintech) usage, consumptive behavior, financial attitude, and financial planning on the personal financial management of Generation Z in Tiban Baru Village, Batam City. A quantitative approach with a descriptive design was employed. Data were collected through a survey of 373 Generation Z respondents who actively use fintech, using a questionnaire instrument. Multiple linear regression analysis was conducted with the assistance of IBM SPSS Statistics 25. The findings reveal that, simultaneously, fintech usage, consumptive behavior, financial attitude, and financial planning have a significant effect on personal financial management, as indicated by an F-count value of 108.008, which exceeds the F-table value of 2.40 at a significance level of 0.000 < 0.05. Partially, fintech usage and financial planning have a positive and significant effect on personal financial management, while consumptive behavior exerts a negative and significant effect. Financial attitude, however, does not have a significant effect on personal financial management, as evidenced by a significance value of 0.089 > 0.05.These findings suggest that optimizing fintech usage and maintaining sound financial planning can enhance the quality of financial management among Generation Z, while consumptive behavior needs to be kept in check. This study carries important implications for the development of behavior-based financial literacy and financial education programs targeting Generation Z.